The impact of β-blockers on outcomes of immune checkpoint inhibitors therapy in advanced lung cancer: a multicenter real-world study - Chang, Lingdan; Zhang, Haitian; Li, Yunxia; Yang, Jilan; Li, Ya; Wang, Guangming; Zhang, Jinsong; Shi, Hongjin; Hai, Bing (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) have improved outcomes in advanced lung cancer. β-adrenergic signaling may promote tumor initiation and progression, and β-blockers (BBs) have emerged as anti-tumor sensitizing agents. This study evaluates the impact of BBs use during ICIs treatment in advanced lung cancer.MethodsThis multicenter retrospective real-world study included 462 patients treated with ICIs from June 2019 to December 2024. Patients were divided into BBs and No BBs groups. Primary endpoints were overall survival (OS) and progression-free survival (PFS); efficacy evaluation and objective response rate (ORR) were secondary. Propensity score matching (PSM) balances baseline characteristics. Kaplan–Meier method, Cox, and logistic regression models were used for survival and multivariate analyses. Subgroup analyses assessed clinical factors. A P value < 0.05 is considered statistically significant.ResultsAfter PSM, 318 patients were included (88 BBs, 230 No BBs). BBs use was associated with longer median PFS (mPFS) (15.8 vs. 11.8 months; HR = 0.67, 95% CI: 0.49–0.92, P = 0.038) and higher ORR (51.1% vs. 35.2%, P = 0.014), but not improved median OS (mOS) (29.0 vs. 31.5 months; HR = 1.38, 95% CI: 0.93–2.03, P = 0.108). BBs use independently predicted improved ORR (OR = 0.45, 95% CI: 0.26–0.78, P = 0.004) and longer PFS (HR = 0.67, 95% CI: 0.49–0.92, P = 0.014). In patients with cardiovascular comorbidities (CVD), BBs use was linked to longer mPFS (15.8 vs. 10.9 months, P = 0.0066) and higher ORR(51.1% vs 27.0%, P<0.001), with no mOS difference (P = 0.82). Among non-small cell lung cancer (NSCLC) patients, mPFS (17.5 vs. 12.3 months, P = 0.04) and ORR (56.0% vs 35.9%, P = 0.004) were also improved in the BBs group, whereas OS did not differ significantly (P = 0.3).ConclusionIn stage-advanced lung cancer, BBs combined with ICIs were associated with improved ORR and prolonged PFS, but did not significantly improve OS. PFS and ORR benefits were also observed in patients with CVD or NSCLC. Further prospective studies are needed to validate these findings and clarify whether BBs directly contribute to ICIs’ efficacy.